Manufacturing of Hybrid Yarn Thermoplastic Composites by the Method of Filament Winding - Ozbay, Burcin; Bekem, Aylin; Unal, Ahmet (GAZI UNIV, 2020)
Filament winding is a manufacturing method to produce composite materials with a thermosetting or thermoplastic matrix impregnated continuous fibers. Due to the high melt viscosity of thermoplastics, some problems such as inadequate fiber dispersion in the structure, low wetting ability, and interface quality problems between matrix and fiber might emerge. Preforms can be used in order to solve these problems in the continuous fiber reinforced composite manufacturing; division of the polymer can be made using either powder or fiber form. In this study, polyethylene/E-glass fiber and polypropylene/E-glass fiber hybrid yarns were used as materials to produce thermoplastic composite structures. Firstly, plate samples were produced at various temperatures, periods of time and different thicknesses of ply. After the preparation of samples tensile test, 3 point bending flexural test, and calcination test were applied and Scanning Electron Microscopy (SEM) observations were also performed to these samples, and then the production parameters were optimized. After that, cylindrical shaped samples were produced by a laboratory-type manual filament winding device and ring stiffness tests were performed. According to the test results of the plate samples, the optimum production conditions were determined as 200 degrees C for 5 minutes for polyethylene/E-glass fiber composite structure and 220 degrees C for 5 minutes for polypropylene/E-glass fiber composite structure. Mechanical test results of plate samples revealed that polypropylene composites presented slightly better results than polyethylene ones. Additionally, in the cylindrical specimens, close results to the ring stiffness values determined by the standards were obtained.
Keywords: Thermoplastic composites; Hybrid yarns; Filament winding; COMMINGLED YARNS; Science & Technology - Other Topics